2007
DOI: 10.2214/ajr.06.0706
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Hepatocellular Carcinoma After Treatment with Yttrium-90 Microspheres

Abstract: Use of combined size and necrosis criteria may lead to more accurate assessment of response to 90Y therapy than use of size criteria alone. Imaging features after 90Y treatment, including size, necrosis, peripheral enhancing nodules, and thin rim enhancement, are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 28 publications
5
76
0
1
Order By: Relevance
“…For these reasons, those authors concluded that the use of combined size and necrosis criteria might lead to a more accurate assessment of response to Yttrium-90 radioembolization than size criteria alone. 29 In our study, RECIST criteria missed all CRs obtained by tumor necrosis and underestimated the extent of partial tumor response because of tissue necrosis. This finding was particularly relevant for patients who received percutaneous ablation.…”
Section: Discussionmentioning
confidence: 54%
“…For these reasons, those authors concluded that the use of combined size and necrosis criteria might lead to a more accurate assessment of response to Yttrium-90 radioembolization than size criteria alone. 29 In our study, RECIST criteria missed all CRs obtained by tumor necrosis and underestimated the extent of partial tumor response because of tissue necrosis. This finding was particularly relevant for patients who received percutaneous ablation.…”
Section: Discussionmentioning
confidence: 54%
“…This difference could be because RECIST evaluates only 1-dimensional tumor measurements and disregards the extent of the necrosis, which is the objective of all locoregional therapy used for HCC, including ablation and intraarterial procedures such as chemoembolization. Considering that a multivariate analysis of survival clearly demonstrated that the complete tumor necrosis was associated with significantly better survival (odds ratio, 1.83; 95% CI, 1.1-3.1; P 5 0.020) (37), the use of combined (size and necrosis) criteria might lead to a more accurate assessment of response to 90 Y radioembolization than criteria based on size alone (38).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, tumor response to therapy has been measured using the standard Response Evaluation Criteria in Solid Tumors (RECIST), which relies on measurements of the greatest dimension of the target lesions (1). However, growing evidence has suggested that evaluation by RECIST may not be the best method for monitoring treatment response in hepatocellular carcinoma (2)(3)(4)(5)(6)(7)(8); the goal of effective locoregional and targeted therapies in hepatocellular carcinoma is to cause tumor necrosis (2,3,(7)(8)(9). As a result of this evidence, the American Association for the Study of Liver Diseases (AASLD) and the European Association for the Study of the Liver (EASL) have proposed the development of superior methods for assessing the response to therapy in hepatocellular carcinoma (3,10,11).…”
Section: Introductionmentioning
confidence: 99%